2017
DOI: 10.1002/jhet.2981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Spirooxindole‐Fused Isoxazoline/Triazole and Isoxazoline/Isoxazole Derivatives from Three‐Component 1,3‐Dipolar Cycloaddition

Abstract: A series of diverse heterocycles containing spirooxindole, isoxazoline/triazole, and isoxazole rings has been synthesized via an efficient three‐component reaction of (E)‐2‐(1‐propargyl‐2‐oxoindoline‐3‐ylidene)acetophenones 1, arylnitrile oxides 2, and arylazides 3 using Cu(I) as catalyst. The regiochemistry and stereochemistry of cycloadducts 4a and 5a have been confirmed by X‐ray diffraction studies. The heterocycles were screened against Gram‐positive and Gram‐negative bacteria and fungi. Several compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…On the basis of our experimental results and previous studies on the reaction mechanism , we propose in Scheme a plausible mechanism for the regioselective and stereoselective dispiropyrrolidine formation.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…On the basis of our experimental results and previous studies on the reaction mechanism , we propose in Scheme a plausible mechanism for the regioselective and stereoselective dispiropyrrolidine formation.…”
Section: Resultsmentioning
confidence: 52%
“…This mechanism has been suggested to explain isomerization in spirooxindole alkaloids , pyrrolidines , and pyrrozilidine derivatives .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid 19a (MIC: 31.2 μg/ml) exhibited promising activity against Gram‐negative E. coli and P. aeruginosa , whereas 19b (MIC: 62.5 μg/ml) displayed considerable activity against Gram‐positive S. aureus and S. pyogenes , and these two hybrids were more potent than ampicillin (MIC: 100–500 μg/ml) against Gram‐negative and Gram‐positive pathogens, respectively. [ 61 ] Isatin–1,2,3‐triazole hybrids 20 and their bis‐1,2,3‐triazole analogs 21 not only possessed potential in vitro and in vivo anticancer activity (MCF‐7, HeLa, and HEK293 cell lines) but also demonstrated great potency against certain bacteria. [ 62,63 ] The SAR revealed that the introduction of the electron‐withdrawing (trifluoromethyl) group at meta ‐position of the phenyl ring and bromo group at ortho ‐position of the phenyl ring had a great influence on the antibacterial and anticancer activity.…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%